Aortic dilatation with bicuspid aortic valves: cusp fusion correlates to matrix metalloproteinases and inhibitors - Ikonomidis, John S. (2011)
BACKGROUND: Congenital bicuspid aortic valves (BAVs) result from fusion of two valve cusps, resulting in left-noncoronary (L-N), right-left (R-L), and right-noncoronary (R-N) morphologies. BAVs predispose to ascending thoracic aortic aneurysms (ATAAs). This study hypothesized that ATAAs with each BAV morphology group possess unique signatures of matrix metalloproteinases (MMPs) and endogenous tissue inhibitors (TIMPs). METHODS: ATAA tissue from 46 BAV patients was examined for MMP/TIMP abundance and global MMP activity compared to normal aortic specimens (n=15). Proteolytic balance was calculated as the ratio of MMP abundance to a composite TIMP score (TS). Results were stratified by valve morphology group (L-N (n=6), R-L (n=31), and R-N(n=9)). RESULTS: The BAV specimens (p<0.05 vs. normal aorta, 100%) displayed elevated global MMP activity (273±63%), MMP-9 (263±47%), and decreased MMP -7 (56±10%), -8 (58±11%), TIMP -1 (63±7%) and -4 (38±3%). The R-L group showed increased global MMP activity (286±89%) and MMP-9 (267±55%) with reduced MMP -7 (45±7%) -8 (68±15%), TIMP -1 (58±7%) and -4 (35±3%). The L-N group showed elevated global MMP activity (284±71%), and decreased MMP-8 (37±17%) and TIMP-4 (48±14). In the R-N group, MMP -7 (46±13%) and -8 (36±17%), and TIMP -1 (59±10) and -4 (42±5%) were decreased. The R-L group demonstrated an increased proteolytic balance for MMP-1, MMP-9, and MMP-12 relative to L-N and R-N. CONCLUSION: Each BAV morphology group possesses a unique signature of MMPs and TIMPs. MMP/TIMP score ratios suggest that the R-L group may be more aggressive, justifying earlier surgical intervention.